2021
DOI: 10.3390/ma14227072
|View full text |Cite
|
Sign up to set email alerts
|

Lignosulfonate-Based Polyurethane Adhesives

Abstract: The feasibility of using lignosulfonate (LS) from acid sulphite pulping of eucalyptus wood as an unmodified polyol in the formulation of polyurethane (PU) adhesives was evaluated. Purified LS was dissolved in water to simulate its concentration in sulphite spent liquor and then reacted with 4,4′-diphenylmethane diisocyanate (pMDI) in the presence or absence of poly(ethylene glycol) with Mw 200 (PEG200) as soft crosslinking segment. The ensuing LS-based PU adhesives were characterized by infrared spectroscopy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…In light of this, we conducted a comparative analysis between the maximum lap shear stress strengths of the PhL-based PU adhesives developed in this study and those previously reported in scientific literature for similar lignin-based PU adhesives. It is worth noting that the lignin used in these previous studies was either functionalized using various methods, such by acetylation, alkylation, amination, depolymerization, solvent extraction, or used directly without any prior chemical modification. , Our results, as depicted in Figure , demonstrates that the adhesion performance achieved in the present study is comparable to, or even surpasses, that reported in earlier work in this area.…”
Section: Resultssupporting
confidence: 76%
“…In light of this, we conducted a comparative analysis between the maximum lap shear stress strengths of the PhL-based PU adhesives developed in this study and those previously reported in scientific literature for similar lignin-based PU adhesives. It is worth noting that the lignin used in these previous studies was either functionalized using various methods, such by acetylation, alkylation, amination, depolymerization, solvent extraction, or used directly without any prior chemical modification. , Our results, as depicted in Figure , demonstrates that the adhesion performance achieved in the present study is comparable to, or even surpasses, that reported in earlier work in this area.…”
Section: Resultssupporting
confidence: 76%
“…In addition to PUF, different types of lignins and LBPs have also been used to prepare other forms of Pus, such as adhesives [ 121 , 127 , 128 ], elastomers [ 129 , 130 , 131 ], coatings [ 132 , 133 ], and films [ 125 ]. Elastomeric PUs are a class of PU materials that have the characteristics of rubber, and their application has increased in recent years due to the high demand for advanced applications such as in biomedicine, shape memory materials, self-healing materials, and gel materials.…”
Section: Lignin As a Building Block To Synthesize Polyurethanesmentioning
confidence: 99%
“…The valorization of SSL has a well-established market for decades, using lignosulfonates as binders (pelletizing of animal feed, ceramics, dust control, fertilizers), dispersants (ceramics, dyes, pigments), emulsifiers (asphalt, inks, waxes), concrete plasticizing agents or adhesives [18,[78][79][80][81]. Most of these applications rely on the good water-solubility of lignosulfonates [81].…”
Section: Sulfite Processmentioning
confidence: 99%